2020
DOI: 10.1007/s12213-020-00127-2
|View full text |Cite
|
Sign up to set email alerts
|

Swarm of magnetic nanoparticles steering in multi-bifurcation vessels under fluid flow

Abstract: Magnetic drug targeting has emerged as a promising approach for enhancing the efficiency of drug delivery. Recent developments in real-time monitoring techniques have enabled the guidance of magnetic nanoparticles (MNPs) in the vascular network. Despite recent developments in magnetic navigation, no comprehensive strategy for swarm of nanoparticles steering under fluid flow exists. This paper introduces a strategy for MNPs steering in a vascular network under fluid flow. In the proposed scheme, the swarm of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…Our previous work identified the effects of particle aggregation on nanoparticles steering [ 24 , 25 ], the results of MD simulation for the membrane crossing in the current work showed that in all crossing conditions (variations in the velocity and direction) the aggregates need a significantly higher crossing work compared to a single particle size under similar conditions. Therefore, reducing the aggregation while maintaining steerability can elevate the drug delivery to the brain.…”
Section: Results and Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our previous work identified the effects of particle aggregation on nanoparticles steering [ 24 , 25 ], the results of MD simulation for the membrane crossing in the current work showed that in all crossing conditions (variations in the velocity and direction) the aggregates need a significantly higher crossing work compared to a single particle size under similar conditions. Therefore, reducing the aggregation while maintaining steerability can elevate the drug delivery to the brain.…”
Section: Results and Discussionmentioning
confidence: 61%
“…The proposed platform was studied using in vitro and in vivo experiments. Models for multiple bifurcation steering have also been developed [ 25 , 26 ], and aggregation under a rotating magnetic field has also been studied [ 27 ]. The proposed models were centered around steering of aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…For hyperthermia treatment, the locomotion of these swarms could be exploited to deliver SPIONs to a tumor site, followed by heating. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Remote magnetic actuation not only provides an unlimited operation time, but also provides the advantage of being able to miniaturize the robot because it does not require batteries. As a part of this miniaturization, magnetic particles also have been studied for various medical purpose such as targeted drug delivery, embolization, and imaging technology [ 9 , 10 , 11 , 12 , 13 ]. These advantages render magnetic robots suitable for minimally invasive medical devices that must operate for a long time inside small and narrow human organs.…”
Section: Introductionmentioning
confidence: 99%